PHYTOCHEMICAL TEST ON METHANOL EXTRACT OF LEAF OF Macaranga hullettii King ex Hook.f. - Rismawati, Rismawati; Marliana, Eva; Daniel, Daniel (JURNAL ATOMIK, 2018)
Phytochemical test of Macaranga hullettii King ex Hook.f have been done. This research aims to find out the secondary metabolites using Thin Layer Chromatography (TLC) from methanol extract on Macaranga hullettii leaf. Based on results of phytochemical screening, it is known that methanol extract contains alkaloid, steroid/triterpenoid, polifenol and flavonoid compounds.